The Mayo Clinic diabetes diet (Good Books, 2011)
Put yourself in charge of reshaping your body and improving your health! The staff at the Mayo Clinic has identified the key habits of people who maintain a healthy weight, and the unhealthy habits of those who don't, and boiled the research down to five good habits to follow-- and five bad habits to break.